Monetary policy implementation with an ample supply of reserves - Gara Afonso; Kyungmin Kim; Antoine Martin; Ed Nosal; Simon M. Potter; Sam Schulhofer-Wohl (Federal Reserve Bank of New York, 2020)
Methods of monetary policy implementation continue to change. The level of reserve supply-scarce, abundant, or somewhere in between-has implications for the efficiency and effectiveness of an implementation regime. The money market events of September 2019 highlight the need for an analytical framework to better understand implementation regimes. We discuss major issues relevant to the choice of an implementation regime, using a parsimonious framework and drawing from the experience in the United States since the 2007-09 financial crisis. We find that the optimal level of reserve supply likely lies somewhere between scarce and abundant reserves, thus highlighting the benefits of implementation with what could be called "ample" reserves. The Federal Reserve's announcement in October 2019 that it would maintain a level of reserve supply greater than the one that prevailed in early September is consistent with the implications of our framework.
Keywords: E42; E58; 330; federal funds market; monetary policy implementation; ample reserve supply